Pelatihan Pengembangan Life Skill Perempuan Dalam Kriya Tekstil Macrame Di Desa Jebak Kecamatan Muara Tembesi Kabupaten Batanghari - Asmarani Putri; Mahdayeni; Zilawati; Dyan Wirdana; Mutiara Aprilia; Suhartini (Yayasan Pelita Negri Belantaraya, Kab. Indragiri Hilir, Prov. Riau, 2024)
ABSTACT Macrame is a classic textile art made by Arab weavers using knotting techniques using rope since the 13th century. The word macrame comes from the word mikramah which means plaiting or hand decoration. Historically, macrame was used to avoid swarms of flies on the riding animals of people in the Middle East. The art of macrame was successful in the 1970s. The implementation of the community service activity program was carried out in the central room of post 13 RT 04, Jebak village, Muara Tembesi sub-district on Saturday 20 January 2024. This service activity took the form of training. This activity was attended by 7 people. This training involved PKK mothers and local teenagers. Keywoards : macramé, life skill